Democratic Republic of Timor-Leste : 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that the non-oil economy of the Democratic Republic of Timor-Leste has grown rapidly in recent years with growth averaging close to 12 percent from 2008 to 2011, allowing the average per capita income to steadily increase. The growth was driven by a rapid increase in government spending, which boosted the public administration and construction sectors. So far, the contributions from agriculture and manufacturing have been modest. Despite falling from the peak of more than 15 percent in 2011, the inflation rate is still in double digits. Executive Directors have welcomed the revised budgetary framework that anticipates a stabilization of government expenditures and revenue diversification.